AN OPTIMIZED LOOP-MEDIATED ISOTHERMAL AMPLIFICATION (LAMP) ASSAY FOR THE DETECTION OF WHITE SPOT SYNDROME VIRUS (WSSV) AMONG CULTURED SHRIMPS IN THE PHILIPPINES - C. M. A. Caipang; M. F. J. Sibonga; J. S. Geduspan; M. J. A. Amar (Journal of Animal and Plant Sciences, 2012)
Loop-mediated isothermal amplification (LAMP) technique is an emerging diagnostic tool for the rapid and sensitive detection of pathogens in aquaculture. In this study, the LAMP assay was evaluated for the detection of the white spot syndrome virus (WSSV), a serious viral pathogen affecting all life stages of penaeid shrimps. The optimum time and temperature conditions for LAMP were 60 min and 65oC, respectively. The assay was highly specific for WSSV and did not cross-react with other shrimp viruses including monodon baculovirus (MBV), infectious hypodermal and hematopoietic necrosis virus (IHHNV) and hepatopancreatic parvovirus (HPV). The limit of detection of the WSSV using the LAMP assay was 5 pg of DNA ml-1 or 5 fg of the genomic DNA per LAMP reaction and was 10 times more sensitive than conventional PCR in detecting the viral pathogen from infected samples. In vivo, both LAMP and conventional PCR were able to detect the virus from tissues of infected shrimp postlarvae. Our  results demonstrated that LAMP is a simple and sensitive method that has potential application as a diagnostic tool in the field for routine detection of WSSV in shrimp aquaculture in the Philippines.
Keywords: WSSV; white spot syndrome virus; loop-mediated isothermal amplification; LAMP; shrimp.